METHODOLOGY OF USING DIGITAL TECHNOLOGIES IN TEACHING COMPUTER SCIENCE - Makhfuza Khabibovna Zohidova (Galaxy International Interdisciplinary Research Journal, 2024)
Digital technologies have revolutionized computer science education, offering new opportunities to enhance learning experiences and develop computational thinking skills. This scientific article presents a comprehensive methodology for the effective integration of digital technologies in the teaching of computer science. The methodology includes core components such as curriculum design, instructional strategies, assessment practices, and professional development to support teachers in using digital tools and platforms. By using this methodology, teachers can create an engaging and interactive learning environment that prepares students for the challenges of the digital age.